Pengaruh Promosi Media Sosial Dan Desain Tempat Terhadap Keputusan Pembelian Di Restoran Bernuansa Jepang - Dede Sudiana; Herma Wiharno; Yanneri Elfa Kiswara (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The purpose of this study is to test: 1) the effect of social media promotion variables on purchasing decisions 2) the effect of place design variables on purchasing decisions This study is aimed at visitors to the Japanese-style restaurant Joglo Arunika, Kuningan Regency. The study uses verification methods with a quantitative approach. The population in this study is the number of visitors to the Joglo Arunika restaurant in Kuningan Regency. The sample in this study amounted to 100 respondents using the Nonprobability Sampling technique, especially spot sampling. Primary data collection was obtained by distributing questionnaires through questionnaire sheets distributed to respondents. This study uses an analysis tool (Partial Least Square) with the Smart-PLS 4 application. The results of this study indicate: 1) social media promotion variables influence purchasing decisions 2) place design variables influence purchasing decisions.